PATOLOGI PEMBANGUNAN ETIKA POLITIK PASCAREFORMASI DALAM PERSPEKTIF POSTSTRUKTURALIS-HIPERSEMIOTIK - Darsono, Darsono; Aprillia, Clara (Journal of Urban Sociology, 2020)
Post-reform Politics in Indonesia marks by development pathologies. The focus of this study covers (1) anomalous symbols in Indonesian politics, (2) the paradoxical development of phenomena that appears in post-reform political ethics. This study uses qualitative method. While, poststructural-hypersemiotic used as a theory. The results show negation or criticism, as is the affirmation of the existence of ethics as a phenomenon that has been drowned by modernist-capitalism, which guerrillas regulates mass ideology through oligarchy of power with development jargon. These anomaly symbols manifest in various aspects, especially in economics, education, law, health and politics; whereas the development paradox is seen in opportunity cost projects and development competition.Kay World: Pathology, anomaly, paradoxes, post-reform, political ethics, hypersemiotics, existentialism-ethical, poststructural.